Pemanfaatan Media Pop Up Book dalam Pembelajaran Bahasa Indonesia untuk Meningkatkan Keterampilan Membaca Nyaring Siswa SD di Kelas Rendah - Sulistyowati, Avivvah; Ekawati, Gressia Fani; Pradita, Hafidz; Ferdian, Luki Eka; Jannah, Miftahul; Sakti, Bayu Purbha (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
The ability to read aloud is an important part of Indonesian language learning in elementary school, especially for lower-grade students who are still in the early stages of developing literacy skills. Students often face difficulties with pronunciation, fluency, and controlling intonation when reading aloud. This article aims to examine the use of pop-up book media in teaching read-aloud skills through a literature study approach. The results of the review show that pop-up books can increase learning motivation, help students understand story context, and strengthen their ability to pronounce words and control intonation while reading. This medium is considered effective as an engaging alternative for reading instruction that aligns with the characteristics of lower-grade students.